PENERAPAN TAM DAN TPB UNTUK MENGIMPLEMENTASIKAN E-COMMERCE BAGI UMKM DI PASAR SENI "SOLO IS SOLO" PASCA PANDEMI COVID-19 - Mutya Paramita Pratita; Dorothea Ririn Indriastuti; Adelia Nur Aszari (JURNAL ILMIAH EDUNOMIKA, 2024)
Technology is always developing and requires society to be able to follow these developments. One of them is in the field of e-commerce. Currently there are many e-commerce platforms available such as Shopee, Tokopedia, Lazada, and others. The platform is expected to make it easier for business people in running their business, especially SMEs. There is a community SMEs are art workers in Surakarta who sell their own artistic products and try to keep up with e-commerce developments. The purpose of this research is to find out the interests of members of the ‘Solo is Solo’ art market in adopting e-commerce to distribute his work to buyers use the TAM and TPB Approach. To achieve this goal, this study uses a questionnaire to explore data that will be filled in by members of the Solo Art Market community of total 72 people, and tested using PLS. As we know that the Covid-19 Pandemic has prevented the art workers from selling their crafts offline. Besides, they tend to choose selling offline than online. Therefore, this study wants to predict their intention to adopt online platforms in order to restore economic conditions after the Covid-19 Pandemic. Keywords : TAM, TPB, SME, Digital Marketing